(untitled) (Bangladesh Journal of Pharmacology, 2014)
The aim of the present work was to study the functional nature of the potential spasmolytic effect of the crude extract of Sauromatum guttaum. It was found positive for the presence of alkaloid and tannins. In isolated rabbit jejunum preparation, S. guttaum caused inhibition of spontaneous and high K+ (80 mM)-induced contractions, with respective EC50 values (95% confidence intervals) of 1.50 mg/mL (0.69-3.02) and 1.17 mg/mL (0.81-1.61), similar to verapamil. Inhibition of high K+ -induced contractions suggests Ca++ antagonistic effect. The Ca++channel blocker activity of S. guttaum was confirmed when pre-treatment of the tissues with extract (0.3-3 mg/mL) caused a rightward displacement in the Ca++ concentration-response curves. Moreover, in the acute toxicity test, S. guttaum was found safe up to the dose of 3 g/kg. The findings of the current study suggest that the S. guttaum exhibited spasmolytic activity, possibly mediated through inhibitory effect on Ca++ entry and was found safe and this current study provides first evidence to the potential use of this plant as antispasmodic and can play a possible role as antidiarrheal.